(untitled) (Journal of actual problems of jurisprudence, 2018)
In the state the general characteristic of compulsory social insurance. And also consider recent developments and shortcomings of social insurance. Social insurance – a system of social security, whose mission – to ensure the constitutional rights of economically active citizens to maintenance in old age, in case of illness. Compulsory social security – part of the state system of social protection. The task today is to build a social security system that could quickly and raise living standards. Keywords: insurance, compulsory insurance, insurance relations, insurance companies.